Psychology of Human Development from an Islamic Perspective - Asmadi Asmadi; Avi Zena; Putri Sarah Naina; Kurnia Rahmayanti (Borong Newinera Publisher, 2026)
This study examines human development from an Islamic perspective by employing a qualitative literature review approach to synthesize classical and contemporary scholarly discussions. Human development is understood not merely as a biological or psychological process, but as a holistic and purposeful progression encompassing physical, cognitive, emotional, and spiritual dimensions. In contrast to dominant Western developmental theories that often prioritize empirical and value-neutral explanations, Islamic thought conceptualizes development as a morally oriented journey guided by divine purpose and ethical responsibility. Data were collected from peer-reviewed journals, academic books, and authoritative Islamic scholarship relevant to psychology, human development, and religious studies. The selected literature was analysed using qualitative content analysis to identify recurring themes, conceptual frameworks, and interpretative differences among scholars. The findings indicate that Islamic perspectives emphasize the integration of bodily growth, intellectual maturity, and spiritual consciousness, with development evaluated not solely by age but by readiness, moral accountability, and social responsibility. Human development is framed as a continuous process directed toward the formation of ethically grounded individuals capable of fulfilling their roles within society. This study further reveals that Islamic developmental thought highlights normative objectives such as moral discipline, self-awareness, and stewardship, which are often underexplored in conventional psychological models. By articulating these dimensions, the study contributes to the enrichment of developmental psychology through a value-based and holistic framework. The findings offer theoretical insights that may inform future research, as well as practical implications for education, counselling, and human development programs that seek to integrate psychological growth with ethical and spiritual values.